A Combined Detection Algorithm for Personal Protective Equipment Based on Lightweight YOLOv4 Model. (4th May 2022) - Ma, Li; Li, Xinxin; Dai, Xinguan; Guan, Zhibin; Lu, Yuanmeng
Abstract : Improper wearing of personal protective equipment may lead to safety incidents; this paper proposes a combined detection algorithm for personal protective equipment based on the lightweight YOLOv4 model for mobile terminals. To ensure high detection accuracy, a channel and layer pruning method (CLSlim) to lightweight algorithm is used to reduce computing power consumption and improve the detection speed on the basis of the YOLOv4 network. This method applies L1 regularization and gradient sparse training on the scaling factor of the BN layer in the convolutional module: global pruning threshold and local safety threshold are used to eliminate redundant channels, the layer pruning threshold is used to prune the structure of the shortcuts in the Cross Stage Partial (CSP) module for inference speed improvement, and finally, a lightweight network model is obtained. The experiment improves the YOLOv4 and YOLOv4-Tiny models for CLSlim lightweight separately in GTX2080ti environment. Results show that (1) CLSlim-YOLOv4 compresses the YOLOv4 model parameters by 98.2% and increases the inference speed by 1.8 times with mAP loss of only 2.1% and (2) CLSlim-YOLOv4-Tiny compresses the original model parameters by 74.3% and increases the inference speed by 1.1 times with mAP increase of 0.8%, which certificates that this improved lightweight algorithm serves better for the real-time ability and accuracy of combined detection on PPE with mobile terminals.